Mineralogy and geochemistry of Miocene tuff from ODP Hole 129-802A - Anne Marie Karpoff; Christian France-Lanord; François Lothe; Philippe Karcher (PANGAEA, 1992)
Drilling at Ocean Drilling Program Site 802 in the central Mariana Basin, northwest Pacific Ocean, revealed an unexpected 222-m-thick sequence of well-cemented tuff of Miocene age. The deposits are unusual in that their source is presumably an unmapped seamount and they exhibit several peculiar petrological and mineralogical features. The well-developed secondary mineral sequence which includes analcime is rare in such relatively young, unburied deposits, in an area where there is little other evidence of hydrothermal activity. The massive tuff section also contains abundant fissure veins made of a rare silicate carbonate sulfate hydroxide hydrate of calcium, called thaumasite, which has not before been described in deep submarine deposits. The smectite-zeolite-thaumasite paragenesis coincides with the presence of chloride and calcium-enriched interstitial waters. The diagenetic evolution of the deposit appears to have been largely controlled by the depositional mode. The discharges of disaggregated and rejuvenated volcaniclasts seem to have been abrupt and repeated. The Miocene tuff at Site 802 thus provides new insights on the interactions between basaltic glass, biogenic phases, and seawater, in a specific deep-sea environment.
Supplement to: Karpoff, AM et al. (1992): Miocene tuff from Mariana Basin, Leg 129, Site 802: a first deep-sea occurrence of thaumasite. In: Larson, RL; Lancelot, Y; et al. (eds.), Proceedings of the Ocean Drilling Program, Scientific Results, College Station, TX (Ocean Drilling Program), 129, 119-135, https://doi.org/10.2973/odp.proc.sr.129.113.1992